Synthesis of novel, functionalised tricycles utilising the interrupted Pummerer reaction. Issue 1 (6th January 2016) - Boyd, Scott; Davies, Robert D.M.; Degorce, Sébastien L.; Groombridge, Sam; S. Scott, James; Stokes, Stephen
Graphical abstract: Abstract: Herein we describe the synthesis of a series of novel, functionalised pyrrolothiazolo–pyrimidines, –pyridines and –pyrazines employing a short reaction sequence, utilising the under-reported interrupted Pummerer reaction to effect cyclisation in the final step.